An alkaline zinc-manganese battery positive electrode and a preparation method thereof
Patent Information
- Application Number
- CN202411909263.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-12-24
AI Technical Summary
由于一次碱性锌锰电池的正极工艺要求正极混合粉料具有97%的高固含量水平,以便于后序的造粒和压片工序的正常进行,因此,CN109841834A的石墨烯浆料分散工艺在一次碱性锌锰电池中无法适用
[0013]由于石墨烯的密度在0.05~0.1g/ml,鳞片石墨和膨胀石墨密度在0.06~0.15g/ml,而电解二氧化锰密度在1.6~1.8g/ml,石墨烯和二氧化锰的密度差异很大,如果两者直接分散,由于密度差异,石墨烯容易在上层,二氧化锰容易下沉,导致石墨烯容易团聚在一起,石墨烯分散开的难度增加,效率降低。 而石墨烯和导电石墨的密度差异不太大,不存在密度差异导致的不均匀性。因此,本发明采用的两步法的固相分散工艺,先将导电石墨和石墨烯混合,利用导电石墨(鳞片石墨和膨胀石墨)刚性的摩擦力结合较高的高速分散线速度,实现高效的打散石墨烯粉体;因为第一步的高速固相分散步骤中石墨烯已经分散开了,第二步的低速固相分散步骤和二氧化锰的混合效率就容易了,相对将石墨烯和二氧化锰进行直接分散,能够实现更高效的分散效率。低速固相分散时将分散的线速度降低,避免过高的分散线速度会对二氧化锰的粒度和结合水的含量造成一定的影响,从而影响电池性能。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of batteries, and more particularly to an alkaline zinc-manganese battery cathode and its preparation method. Background Technology
[0002] As a traditional energy storage element, the basic structure of a primary alkaline zinc-manganese battery consists of a positive electrode, a negative electrode, a separator, an electrolyte, a positive current collector, and an outer steel casing. The capacity of an alkaline manganese battery is typically limited by the positive electrode, which is mainly composed of electrolytic manganese dioxide, a conductive agent, and a binder. Electrolytic manganese dioxide serves as the active material, but its intrinsic conductivity is low (10⁻⁶ Ω·cm). -3 ~10 -5 (S / cm), therefore, a conductive agent with excellent conductivity is needed to enhance its conductivity. Currently, the conductive agent used in the positive electrode of alkaline manganese batteries is usually conductive graphite.
[0003] Workers in the alkaline manganese battery industry have been pursuing higher battery discharge performance, primarily through technological innovation and material improvements. Chinese patent CN109841834A discloses a composite conductive agent for lithium-ion batteries, which improves the conductivity of the positive electrode by combining acetylene black, conductive graphite, carbon nanofibers, carbon nanotubes, and graphene. Chinese patent CN114695895A discloses incorporating conductive agents with better conductivity, such as carbon nanotubes and graphene, into the conductive agent of the positive electrode of lithium manganese coin cells to enhance the battery discharge performance. However, there is still room for improvement and optimization in the electrical performance of all battery types (including primary alkaline zinc-manganese batteries).
[0004] Furthermore, graphene has a large specific surface area (BET: 20-35m²). 2 = / g), easily agglomerates, which not only reduces its own adsorption capacity but also affects the excellent performance of graphene itself. In order to achieve uniform dispersion of graphene, Chinese patent CN109841834A pre-dissolves graphene, carbon nanofibers, and carbon nanotubes in NMP organic solvent and performs wet mixing to obtain a uniformly dispersed conductive slurry. Since the cathode process of primary alkaline zinc-manganese batteries requires the cathode mixed powder to have a high solid content of 97% to facilitate the subsequent granulation and tableting processes, the graphene slurry dispersion process of CN109841834A is not applicable to primary alkaline zinc-manganese batteries. In addition, Chinese patent CN114695895A pre-disperses graphene, carbon nanofibers, and carbon nanotubes in an aqueous solution, then wet-mixes them with cathode powders such as manganese dioxide, and finally requires vacuum drying of the cathode mixture to remove excess moisture. This method requires an additional vacuum drying process and vacuum drying equipment. Summary of the Invention
[0005] The first objective of this invention is to provide an alkaline zinc-manganese battery cathode that uses the specific surface area ratio between the conductive agent and electrolytic manganese dioxide, as well as the total conductivity of the conductive agent and electrolytic manganese dioxide, as screening conditions to determine the alkaline zinc-manganese battery formulation that yields good battery performance. This achieves more precise control over the content of conductive agent and electrolytic manganese dioxide in the alkaline zinc-manganese battery formulation, which is beneficial for further improving battery performance.
[0006] An alkaline zinc-manganese battery cathode comprises electrolytic manganese dioxide and a conductive agent, wherein the conductive agent comprises graphene; the addition ratio of the conductive agent to electrolytic manganese dioxide is 2.95–4:96–97.05, and simultaneously satisfies the following two conditions: the total surface area of the conductive agent / the total surface area of the electrolytic manganese dioxide = 0.025–0.037 and the total conductivity of the conductive agent and the electrolytic manganese dioxide ≥ 1.5 S / cm.
[0007] In existing technologies, the appropriateness of the amount of conductive agent is usually evaluated by the battery discharge performance index, and suitable conductive agent formulations and dosages are selected. However, this ignores the fundamental factors affecting battery performance, and the selection results are not accurate enough.
[0008] The inventors of this invention derived their understanding from the positive electrode reaction mechanism of a primary alkaline zinc-manganese battery: MnO2 + H2O + e-. - —MnOOH +Starting from this point, considering that electrons need to enter the manganese lattice from the interface between electrolyzed manganese dioxide and the conductive agent during the reaction at the positive electrode, achieving good battery performance requires two core conditions: first, both manganese dioxide and the conductive agent must have sufficiently high conductivity; second, there must be a sufficiently large contact area between them. The matching relationship of the specific surface area between manganese dioxide and the conductive agent, as well as their corresponding total conductivity, will vary with changes in the type and proportion of the conductive agent and the proportion of electrolyzed manganese dioxide. Therefore, the inventors uniformly mixed the conductive agent and electrolytic manganese dioxide to obtain a composite powder. They studied the relationship between the surface area ratio of the conductive agent to the electrolytic manganese dioxide, the conductivity of the composite powder (i.e., the total conductivity of the conductive agent and electrolytic manganese dioxide), and battery performance. Using "total surface area of the conductive agent / total surface area of electrolytic manganese dioxide = 0.025~0.037" and "total conductivity of the conductive agent and electrolytic manganese dioxide ≥ 1.5 S / cm" as screening criteria, they determined the alkaline zinc-manganese battery formulation corresponding to good battery performance. Since both "total surface area of the conductive agent / total surface area of electrolytic manganese dioxide" and "total conductivity of the conductive agent and electrolytic manganese dioxide" are determined by the composition and amount of the conductive agent, more precise control over the content of the conductive agent and electrolytic manganese dioxide in the alkaline zinc-manganese battery formulation can be achieved. Furthermore, the research results found that when the above screening conditions are met, the ratio of the conductive agent to electrolytic manganese dioxide can reach below 4:96 (specifically: 2.95 to 4:96 to 97.05), which can maximize the amount of electrolytic manganese dioxide used, thereby improving the energy density of the battery under low current while also showing a significant improvement in the rate performance of the battery under medium and high current.
[0009] Furthermore, the positive electrode of the alkaline zinc-manganese battery also includes potassium hydroxide electrolyte and binder, wherein the potassium hydroxide electrolyte is 1-3% and the binder is 0.1-0.6%.
[0010] Furthermore, the conductive agent further includes conductive graphite, which is flake graphite and / or expanded graphite. Preferably, the graphene content in the conductive agent is controlled at 10-60%. Even further, the conductive agent is composed of flake graphite, expanded graphite, and graphene, wherein the flake graphite comprises 20-50%, the expanded graphite 30-70%, and the graphene 10-30%.
[0011] Furthermore, the graphene is selected with a specific surface area ≥ 20 m². 2 / g of graphene. Using graphene, which already has a large specific surface area, helps reduce the amount of graphene and composite conductive agent needed. The microstructure of the graphene can be multilayered or monolayered.
[0012] The second objective of this invention is to provide a preparation process for the above-mentioned alkaline zinc-manganese battery cathode, comprising the following steps: (1) The two-step solid-phase dispersion process; ① High-speed solid-phase dispersion: The conductive agent is composed of conductive graphite and graphene. The graphene and conductive graphite are first pre-dispersed uniformly by high-speed stirring, with a dispersion linear velocity of 8m / s ≤ 12m / s and a dispersion time of 10min ≤ 30min, to obtain composite conductive agent powder. ② Low-speed solid-phase dispersion: Electrolytic manganese dioxide is added to the composite conductive agent powder obtained in the high-speed solid-phase dispersion step and dispersed uniformly at a low speed, where 2m / s≤dispersion linear velocity≤4m / s and 10min≤dispersion time≤20min, to obtain positive electrode powder; (2) Potassium hydroxide electrolyte is sprayed into the positive electrode powder obtained in step (1) and wet-mixed evenly to obtain alkaline zinc-manganese battery positive electrode mix.
[0013] Because graphene has a density of 0.05–0.1 g / ml, flake graphite and expanded graphite have a density of 0.06–0.15 g / ml, while electrolytic manganese dioxide has a density of 1.6–1.8 g / ml, the density difference between graphene and manganese dioxide is significant. If they are directly dispersed, due to this density difference, graphene tends to rise to the top while manganese dioxide tends to sink, causing graphene to easily agglomerate. This increases the difficulty of dispersing graphene and reduces efficiency. However, the density difference between graphene and conductive graphite is not significant, and there is no inhomogeneity caused by density differences. Therefore, the two-step solid-phase dispersion process employed in this invention first mixes conductive graphite and graphene. The rigid friction of the conductive graphite (flake graphite and expanded graphite) combined with a high-speed dispersion linear velocity achieves efficient dispersibility of the graphene powder. Because the graphene is already dispersed in the first high-speed solid-phase dispersion step, the mixing efficiency with manganese dioxide in the second low-speed solid-phase dispersion step is easier. Compared to directly dispersing graphene and manganese dioxide, this achieves higher dispersion efficiency. During low-speed solid-phase dispersion, the dispersion linear velocity is reduced to avoid excessively high dispersion linear velocities affecting the particle size of manganese dioxide and the content of bound water, thereby impacting battery performance. Detailed Implementation
[0014] The preferred embodiments of the alkaline zinc-manganese battery cathode and its preparation method of the present invention are described in detail below.
[0015] An alkaline zinc-manganese battery cathode comprises electrolytic manganese dioxide and a conductive agent, wherein the conductive agent comprises graphene; the addition ratio of the conductive agent to electrolytic manganese dioxide is 2.95–4:96–97.05, and simultaneously satisfies the following two conditions: the total specific surface area of the conductive agent / the specific surface area of the electrolytic manganese dioxide = 0.025–0.037 and the total conductivity of the composite conductive agent and the electrolytic manganese dioxide ≥ 1.5 S / cm.
[0016] During the experimental phase, the inventors combined different formulations of conductive agents and electrolytic manganese dioxide according to the proportions shown in Table 1 (conductive agent content ranging from 2.95% to 4%), and mixed them using conventional stirring and mixing processes (linear speed of 1-2 m / s) to obtain composite powders. During the mixing process, samples were taken at regular intervals to test the carbon content at different locations to determine the uniformity of the mixture, and the mixing time (i.e., dispersion time) required for uniform mixing was recorded. The specific surface area (BET) of electrolytic manganese dioxide and the specific surface area (BET) of various conductive agents were tested using a dynamic method, and the ratio of the total surface area of electrolytic manganese dioxide to the total surface area of the conductive agents was calculated based on their amounts in the battery. The conductivity of the composite powder was then tested.
[0017] Table 1
[0018] As shown in Table 1, when the ratio of the total surface area of the conductive agent to the total surface area of electrolytic manganese dioxide is between 0.025 and 0.037, and the total conductivity of the conductive agent and electrolytic manganese dioxide is ≥1.5 S / cm, the corresponding addition ratio of the conductive agent to electrolytic manganese dioxide is 2.95–4:96–97.05. Compared with the current traditional alkaline zinc-manganese battery, the proportion of conductive agent is lower, while the proportion of electrolytic manganese dioxide is higher, which is beneficial to improving battery performance. Furthermore, due to the addition of graphene to the conductive agent, the traditional mixing process for alkaline manganese batteries requires a longer dispersion time, resulting in a significant decrease in the efficiency of uniform mixing. Moreover, the higher the proportion of graphene added, the longer the time required to achieve uniform mixing.
[0019] Add 0.4% binder to the uniformly mixed composite powder, mix thoroughly, spray in potassium hydroxide electrolyte, wet mix evenly, then roll, granulate, sieve, and press into a positive electrode ring for the LR6 alkaline manganese battery, and assemble into an LR6 alkaline manganese battery. After standing at room temperature (20±2℃) for 1 week, conduct electrical performance tests, including testing the battery's internal resistance, and selecting high, medium, and low current modes for battery performance testing. For discharge performance, Comparative Example 1 is used as 100%.
[0020] Table 2
[0021] As shown in Table 2, the internal resistance of the battery decreased to varying degrees with the addition of graphene material. Furthermore, the discharge performance (performance improvement and uniformity) of the battery under low, medium, and high currents was closely related to the ratio of the total surface area of the conductive agent to the total surface area of electrolytic manganese dioxide and the conductivity of the composite powder. When the ratio of the total surface area of the conductive agent to the total surface area of electrolytic manganese dioxide was too low (Comparative Examples 1 to 7), the uniformity of the battery under high current discharge was unsatisfactory (below 90%), presumably due to insufficient conductive agent area and inadequate consistency of the conductive network. Ensuring that the total surface area of the conductive agent / the total surface area of the active material electrolytic manganese dioxide meets the requirements of this invention can reduce the amount of conductive agent used and increase the proportion of the active material electrolytic manganese dioxide (in this invention, the ratio of conductive agent to manganese dioxide can be reduced to a minimum of 2.95:97.05). The battery's discharge uniformity under various current modes remained above 95%, and the performance was significantly improved under all tested current densities (low, medium, and high). When the ratio of the total surface area of the conductive agent to electrolytic manganese dioxide is greater than 0.037 (Comparative Example 8), although the conductivity is also high, the discharge performance under both high and low currents does not increase, and the discharge performance under medium current even decreases to some extent. In addition, the increased proportion of graphene in the conductive agent leads to a longer dispersion time, and the uniformity of battery performance is also relatively poor. When the ratio of the conductive agent to electrolytic manganese dioxide exceeds 4:96 (Comparative Example 9), due to the decreased proportion of the active material manganese dioxide, all performance characteristics show a certain degree of decline, especially the low-current performance, which shows a more significant decrease.
[0022] Furthermore, as can be seen from the above embodiments and comparative examples, the addition of graphene using conventional mixing processes (linear speed of 2 m / s) requires a relatively long mixing time, significantly reducing mixing efficiency. Moreover, the higher the proportion of graphene, the more difficult the mixing process becomes.
[0023] The inventors also prepared composite powder using a two-step solid-phase dispersion process, following the same composite conductive agent formulation of "60% expanded graphite / 40% graphene" (same as in Example 10 above). The two-step solid-phase dispersion process is as follows: ① High-speed solid-phase dispersion: Graphene and expanded graphite are first pre-dispersed uniformly by high-speed stirring to obtain composite conductive agent powder; ② Low-speed solid-phase dispersion: Electrolytic manganese dioxide is added to the composite conductive agent powder obtained in the high-speed solid-phase dispersion step for low-speed uniform dispersion. The dispersion linear velocity is 2m / s to obtain positive electrode powder (i.e., the composite powder).
[0024] The dispersion time required to achieve uniform mixing of the composite conductive agent powder at different linear velocities was recorded (see Table 3 below). Furthermore, the change in the average particle size of the composite conductive agent powder after dispersion at different linear velocities was used to determine whether the linear velocity would damage the physical properties of the conductive powder.
[0025] Table 3
[0026] The experimental results in Table 3 show that the dispersion time decreases significantly with increasing linear velocity. Increasing the linear velocity from 12 m / s to 15 m / s in high-speed solid-phase dispersion has little impact on dispersion efficiency. Furthermore, the particle size analysis of the conductive agent after dispersion reveals a significant decrease in particle size of the composite conductive agent powder after increasing the linear velocity to 15 m / s, suggesting a certain degree of damage to the conductive graphite particles. Therefore, the optimal dispersion linear velocity for solid-phase dispersion is 12–15 m / s. At this velocity, the dispersion time for high-speed solid-phase dispersion is only 15 min, far shorter than the 60 min required for conventional dispersion linear velocities (1–2 m / s), resulting in a significant improvement in dispersion efficiency.
[0027] Therefore, the preparation process of the alkaline zinc-manganese battery cathode of the present invention includes the following steps: (1) The two-step solid-phase dispersion process; ① High-speed solid-phase dispersion: The composite conductive agent is composed of conductive graphite and graphene. The graphene and conductive graphite are first pre-dispersed uniformly by high-speed stirring, with a dispersion linear velocity of 8m / s ≤ 12m / s and a dispersion time of 10min ≤ 30min, to obtain composite conductive agent powder. ② Low-speed solid-phase dispersion: Electrolytic manganese dioxide is added to the composite conductive agent powder obtained in the high-speed solid-phase dispersion step and dispersed uniformly at a low speed, where 2m / s≤dispersion linear velocity≤4m / s and 10min≤dispersion time≤20min, to obtain positive electrode powder; (2) Potassium hydroxide electrolyte is sprayed into the positive electrode powder obtained in step (1) and wet-mixed evenly to obtain alkaline zinc-manganese battery positive electrode mix.
[0028] Generally, in the alkaline zinc-manganese battery positive electrode, the potassium hydroxide electrolyte is controlled at 1-3%, and the binder is controlled at 0.1-0.6%. The binder can be added together with the electrolytic manganese dioxide in step ②, or it can be added to the positive electrode powder after step ②.
[0029] The conductive agent can be entirely graphene, or it can be a composite conductive agent composed of graphene and conductive graphite. The conductive graphite can be flake graphite and / or expanded graphite.
[0030] When the conductive graphite is composed of flake graphite and expanded graphite, the composite conductive agent contains 20-70% flake graphite, 20-90% expanded graphite, and 10-60% graphene.
[0031] Preferably, the graphene is selected with a specific surface area ≥ 20 m². 2 / g of graphene. Using graphene, which already has a large specific surface area, helps reduce the amount of graphene and composite conductive agent needed. The microstructure of the graphene can be multilayered or monolayered.
[0032] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. An alkaline zinc-manganese battery positive electrode, comprising electrolytic manganese dioxide and a conductive agent, characterized in that, The composition of the conductive agent is selected from either of the following two cases: (1) composed of graphene and expanded graphite; (2) composed of graphene, expanded graphite and flake graphite. When the conductive agent is case (1), the graphene mass percentage is 10-60% based on the total mass of the conductive agent; the mass ratio of the conductive agent to electrolytic manganese dioxide is 2.95-4:96-97.
05. When the conductive agent is case (2), the mass percentage of flake graphite is 20-50%, the mass percentage of expanded graphite is 30-70%, and the mass percentage of graphene is 10-30% based on the total mass of the conductive agent; the mass ratio of the conductive agent to electrolytic manganese dioxide is 2.95-4:96-97.
05. Furthermore, for any of the above situations, the following conditions must be met simultaneously: the total surface area of the conductive agent / the total surface area of electrolytic manganese dioxide = 0.025 to 0.037 and the total conductivity of the conductive agent and the electrolytic manganese dioxide ≥ 1.5 S / cm.
2. The alkaline zinc-manganese battery positive electrode according to claim 1, characterized in that: The positive electrode of the alkaline zinc-manganese battery also includes potassium hydroxide electrolyte and binder, wherein the potassium hydroxide electrolyte is 1-3% and the binder is 0.1-0.6%.
3. The alkaline zinc-manganese battery positive electrode according to claim 1, characterized in that: The conductive agent also includes conductive graphite, which is flake graphite and / or expanded graphite.
4. The alkaline zinc-manganese battery positive electrode according to claim 1, characterized in that: The graphene used is graphene with a specific surface area ≥ 20 m² / g.
5. The preparation process of the alkaline zinc-manganese battery cathode as described in claim 1, comprising the following steps: (1) The two-step solid-phase dispersion process; ① High-speed solid-phase dispersion: The conductive agent is composed of conductive graphite and graphene. The graphene and conductive graphite are first pre-dispersed uniformly by high-speed stirring, with a dispersion linear velocity of 8m / s ≤ 12m / s and a dispersion time of 10min ≤ 30min, to obtain composite conductive agent powder. ② Low-speed solid-phase dispersion: Add the electrolytic manganese dioxide to the composite conductive agent powder obtained in the high-speed solid-phase dispersion step and disperse it uniformly at a low speed, where 2m / s≤dispersion linear velocity≤4m / s and 10min≤dispersion time≤20min, to obtain positive electrode powder; (2) Potassium hydroxide electrolyte is sprayed into the positive electrode powder obtained in step (1) and wet-mixed evenly to obtain alkaline zinc-manganese battery positive electrode mix.
Citation Information
Patent Citations
Composite conductive agent, preparation method thereof and application of composite conductive agent in positive electrode slurry
CN109841834A
Lithium-manganese button cell positive electrode material doped with graphene, preparation method and application
CN114695895A
Preparation device and preparation method of alkaline battery positive electrode
CN113964286A
Alkaline zinc-manganese battery
CN114759205A